Medical care of transgender athletes and policy implications: ACSM contemporary issue statement - Marra, J.; Christensen, D.; Harper, J. M.; Iwamoto, S. J.; Ryan, W.; Safer, J. D.; Streed, C. G.; Nokoff, N. J.; Moreau, K. L. (Medicine & Science in Sports & Exercise, 2026)
Although transgender and gender diverse people make up 0.6% of the population in the United States, they are underrepresented in sports. Transgender athletes are increasingly visible and subject to widely discrepant policies regarding their participation in sports. This Contemporary Issues statement reviews topics relevant to the care of transgender athletes, for the providers, trainers, coaches, and others caring for this population. We review: 1) barriers to sport participation, 2) a review of gender-affirming medical and surgical care and the impacts on factors related to sport performance, 3) mental health considerations, and 4) a framework for understanding stressors and resilience. Most of the available data included here are from nonathlete transgender people, with limited data in transgender athletes. More robust data in transgender athletes are needed for future policies.